Genetic structure of the collection of ryegrass (Lolium) cultivars: a study based on SSR and SCoT markers - Yu. M. Mavlyutov; E. A. Vertikova; A. O. Shamustakimova; I. A. Klimenko (Труды по прикладной ботанике, генетике и селекции, 2023)
Background. Current molecular and genetic approaches make it possible to accelerate ryegrass breeding, simplify source material evaluation, and increase its accuracy. The efficiency of PCR-based SSR and SCoT marker techniques was studied in the context of evaluating the genetic structure of annual and perennial ryegrass accessions and defining DNA-identifying markers.Materials and methods. Genomic DNA was isolated from the aggregate sample of 30 seedlings from each of the 15 analyzed cultivars according to the modified SDS DNA extraction protocol. In total, 20 SSR and 22 SCoT markers were used to assess genetic polymorphism. Basic parameters of the markers’ informative efficiency were identified. Genetic relationships among the studied cultivars were analyzed on the basis of the Neighbor-Joining dendrogram and Bayesian model.Results. To assess the genetic polymorphism of ryegrass species and varieties, 7 SSR loci were selected, for which 110 allelic variants were identified (34 alleles were unique for individual cultivars), and 9 SCoT loci, for which 78 polymorphic amplification fragments were identified, with 28 being cultivar-specific. The dendrogram of genetic similarity and modeling in the Structure v2.3.4 program according to the results of SSR and SCoT analyses distributed the cultivars by their traits according to their species, ploidy level, origin, and similarity. Based on PCoA, carried out using summarized data of SSR and SCoT analyses, a multidimensional diagram of genetic relationships among ryegrass cultivars was constructed.Conclusions. The systems of SSR and SCoT markers appeared to be an efficient tool to reveal genetic polymorphism and identify differences among ryegrass species and cultivars. We found unique DNA profiles that can be used for genetic identification. The results of the study have practical significance in cultivar-specific identification and selection of cultivars for various purposes.